O Programa Dinheiro Direto na Escola (PDDE) interativo como ferramenta de gestão escolar: uma proposta de formação para Rede Pública Municipal de Ensino de Barueri - SP - Gonçalves, Andréa (2016)
This study aims to organize a training proposal to qualify school managers in the use of the Programa Dinheiro Direto na Escola (PDDE) Interativo platform, as a management tool to meet their demands and possible improvements in the Elementary schools of the municipal public network of Barueri ,in the metropolitan area of São Paulo. From this perspective, the work situates the PDDE Interativo within a historical context of educational policies, as well as conceptual information on its methodology; analyzes official texts and discusses issues focusing on school management, strategic management, strategic planning and training of school management. The research developed shows an association between the qualitative and quantitative approach involving research and analysis of PDDE Interativo platform and the information contained in the Action Plan, in addition to the interview with three of the network school principals. It was observed that the platform enables the school perform an analysis of context by different dimensions and the Action Plan is an instrument that points the largest selected challenges as well as possible routes to confront them, expressed through actions and strategies. In addition, it highlights the need for training to use the platform as a management tool not merely to fulfill its fill. Given this reality, the proposed training for the use of the PDDE Interativo platform is presented as a management tool targeting public school managers and other school actors working in the network